1964
DOI: 10.1063/1.1711076
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Stability of Couette Motion with a Radial Thermal Gradient

Abstract: An experimental study has been made of the hydrodynamic stability of viscous flow between coaxial rotating cylinders with a superposed radial thermal gradient. For the data presented, the outer cylinder is at rest and the annulus is small. The axis of the cylinders is vertical; the fluid is water. There is a qualitative difference between the type of instability which first sets in when the thermal gradient is zero or nonzero: the secondary motion when the gradient is nonzero does not consist of toroidal Taylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…In comparison to the periodic case, this intersection point is displaced to ðRe; RaÞ ¼ ð66; 257:02Þ because of the finite aspect-ratio. Here, as in the periodic case, and long aspect-ratio experiments of Snyder and Karlson [6], who used C ¼ 337, there is a region in which spiral modes appear at lower values of Re than Taylor vortices. However, this region is limited by a turning point and when Ra is further increased instabilities are suppressed.…”
Section: Axially Bounded Cylindersmentioning
confidence: 89%
See 1 more Smart Citation
“…In comparison to the periodic case, this intersection point is displaced to ðRe; RaÞ ¼ ð66; 257:02Þ because of the finite aspect-ratio. Here, as in the periodic case, and long aspect-ratio experiments of Snyder and Karlson [6], who used C ¼ 337, there is a region in which spiral modes appear at lower values of Re than Taylor vortices. However, this region is limited by a turning point and when Ra is further increased instabilities are suppressed.…”
Section: Axially Bounded Cylindersmentioning
confidence: 89%
“…The first group of experiments [6][7][8] is characterised by long cylinders C ¼ h=ðr o À r i Þ P 100 and narrow gap g ¼ r i =r o K 1. Ali and Weidman [9] performed a detailed linear stability analysis of such flows using axial periodicity and reported on the influence of the Prandtl number (r) and g on the stability boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The last term in (28) induces an asymmetry between the case with positive ∆T and negative ∆T . An experimental study by Snyder and Karlsson [47] helps to quantifying the role of dissipative processes. It was found that both positive and negative ∆T have a stabilizing effect when ∆T is small, and a destabilizing effect when ∆T is large.…”
Section: Radial Stratificationmentioning
confidence: 99%
“…According to the experimental observations of Snyder and Karlson [20][21][22], the flow configuration remains axisymmetric when the magnitude of the radial temperature gradient across the annular gap is less than ±5°C/cm. Hence, the temperature gradient considered here is restricted to satisfy this criterion.…”
Section: Physical Model and Mathematical Formulationmentioning
confidence: 91%